Analysis of Consumer Attitudes and Behavior Towards Kebab Skin Stick Snacks (STIKBAB) in Bogor City - Rima Rachmawati; Mohammad Wartaka; Wartoyo Hadi (The Management Journal of Binaniaga, 2022)
This study aims to determine the priority scale of attributes, attitudes and behavior, as well as determine the formulation of a marketing mix strategy for snack products, Sticks Skin Kebab (STIKBAB). Sources of data in this study obtained from 98 respondents in the city of Bogor. Statistical analysis used in this study includes analysis of the multi-attribute fishbein model, subjective norms and theory of reasoned action. The results of the fishbein analysis on the evaluation of attributes from the most important to the least important in a row are the quality of raw materials, ease of obtaining, affordable prices, attractive promotions, attractive packaging, varied product types, and brands with a score of 1.57 each. , 1.54, 1.53, 1.49, 1.45, 1.36, 1.26. Meanwhile, consumer attitudes towards the brand are 44.94 which illustrates good consumer attitudes and tends to make repeat purchases. From the behavioral model, it appears that of the seven attributes analyzed have a positive B~BI value (greater than zero) this means that consumer behavior in STIKBAB is good or positive. The marketing strategy that can be taken is to maintain the trust value for the attributes that are most important to consumers (evaluation) and increase the attributes that are still not able to meet the requirements of consumer evaluation.